To expand the expression \((3x - 5)(x^2 + x + 5)\), we can use the distributive property (also known as the FOIL method for binomials).
-
Distribute \(3x\) to each term in \((x^2 + x + 5)\): \[ 3x \cdot x^2 = 3x^3 \] \[ 3x \cdot x = 3x^2 \] \[ 3x \cdot 5 = 15x \]
-
Now distribute \(-5\) to each term in \((x^2 + x + 5)\): \[ -5 \cdot x^2 = -5x^2 \] \[ -5 \cdot x = -5x \] \[ -5 \cdot 5 = -25 \]
-
Combine all these results: \[ 3x^3 + 3x^2 + 15x - 5x^2 - 5x - 25 \]
-
Now combine like terms:
- The \(x^2\) terms: \(3x^2 - 5x^2 = -2x^2\)
- The \(x\) terms: \(15x - 5x = 10x\)
-
Write the final expression in standard form: \[ 3x^3 - 2x^2 + 10x - 25 \]
Thus, the expanded expression in standard form is: \[ \boxed{3x^3 - 2x^2 + 10x - 25} \]